Predicting soil erosion and assessing quality indicators in two Brazilian watersheds: subsidy for territorial planning - Salomão, Fernanda Sota [UNESP]; Silva, Alexandre Marco da [UNESP] (Taylor & Francis, 2021)
Soil erosion might be induced by human pressure and result in irreversible environmental impacts. In the municipality of Itapevi (SP, Brazil), where demographic saturation has driven the population to the outskirts of the urban center, changes in land cover and the occupation of environmentally fragile areas of the relief can trigger the erosion process. Hence, we aimed to evaluate erosion susceptibility in two hydrographic sub-basins of Sapiantã. We considered soil quality-related and active erosion occurrence, associated with the Universal Soil Loss Equation. The results indicated that despite strong Natural Potential Erosion, the areas showed soil losses predominantly below 10 t.ha−1.year−1, due to the significant vegetation cover present. The advance of unplanned urbanization in the watershed may contribute to the siltation of water bodies and floods in the central area of the municipality, making it necessary to adopt efficient public policies in preventing soil loss by sheet erosion.
Keywords: Land cover change; loss equation; natural potential for erosion; sheet erosion; susceptibility for erosion; universal soil